2018
DOI: 10.1093/intimm/dxy011
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic treatment during neonatal age provides optimal protection against experimental asthma through the modulation of microbiota and T cells

Abstract: The incidence of allergic diseases, which increased to epidemic proportions in developed countries over the last few decades, has been correlated with altered gut microbiota colonization. Although probiotics may play a critical role in the restoration of gut homeostasis, their efficiency in the control of allergy is controversial. Here, we aimed to investigate the effects of probiotic treatment initiated at neonatal or adult ages on the suppression of experimental ovalbumin (OVA)-induced asthma. Neonatal or ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…The offspring showed reduced expression of TNF-α, IFN-γ, IL-5, and IL-1 in splenocytes, and reduced allergic airway and peribronchial inflammation in the lung [146]. In a recent OVA-induced asthma mouse model, probiotic oral treatment with combined Lactobacilli casei/lactis/acidophilus plus Bifidobacteria bifidium/lactis reduced allergic airway disease when given perinatally [147]. In gut microbiota, higher Firmicutes and Actinobacteria appeared when probiotics were applied at neonatal age, accompanied by higher CD4+ Tregcell numbers in BALF and increased caecal butyrate, whereas only Actinobacteria were significantly higher compared to sham-treated mice when probiotics were applied to adult animals.…”
Section: Asthma Prevention I) Probioticsmentioning
confidence: 99%
“…The offspring showed reduced expression of TNF-α, IFN-γ, IL-5, and IL-1 in splenocytes, and reduced allergic airway and peribronchial inflammation in the lung [146]. In a recent OVA-induced asthma mouse model, probiotic oral treatment with combined Lactobacilli casei/lactis/acidophilus plus Bifidobacteria bifidium/lactis reduced allergic airway disease when given perinatally [147]. In gut microbiota, higher Firmicutes and Actinobacteria appeared when probiotics were applied at neonatal age, accompanied by higher CD4+ Tregcell numbers in BALF and increased caecal butyrate, whereas only Actinobacteria were significantly higher compared to sham-treated mice when probiotics were applied to adult animals.…”
Section: Asthma Prevention I) Probioticsmentioning
confidence: 99%
“…Mice studies showed that administration of Bifidobacterium breve or adolescentis strains and Lactobacillus plantarum or rhamnosus strains significantly decreased allergic airway inflammation in OVA‐ or birch pollen‐induced asthma mice models . It is worthy to note that the effect of pro‐biotics in mice asthma models is more prominent in neonates than adults …”
Section: Therapeutic Value Of the Microbiome Insights For Asthma: Promentioning
confidence: 99%
“…After sensitization, a challenge step induces allergic inflammation, which involves re-exposure of the animal to the allergen via the administration route typical for a given allergic disease. For instance, in allergic airway disease models, an inflammatory response is evoked in the airways by repeated exposures (or challenges) to the allergen, through either aerosol inhalation ( Mendes et al, 2017 ; Pellaton et al, 2012 ) or intranasally ( Nunes et al, 2018 ; Wu et al, 2016 ). We list examples of such models in Table 1 .…”
Section: The Use Of Mouse Models In Probiotic Researchmentioning
confidence: 99%
“…This release of pro-inflammatory mediators in the airways also leads to airway hyperreactivity (AHR; Box 1 ), hypersecretion of mucus, airway tissue remodelling and other manifestations reminiscent of asthma-associated chronic allergic airway inflammation in humans ( Nials and Uddin, 2008 ). As a result, allergic airway inflammation is typically assessed based on differential counts of inflammatory cells, such as eosinophils and neutrophils, in the bronchoalveolar lavage fluid (BALF; Box 1 ) ( Jan et al, 2012 ; Karimi et al, 2009 ; Nunes et al, 2018 ; Pellaton et al, 2012 ) ( Table 1 ). Airway function is assessed based on airway resistance measurements with invasive ( MacSharry et al, 2012 ) and noninvasive (e.g.…”
Section: The Use Of Mouse Models In Probiotic Researchmentioning
confidence: 99%
See 1 more Smart Citation